DIFFICULTIES OF APPLYING PARTICLE 了 LE IN CHINESE - Gorbatenko, Olga; Ageev, Nicolay (International Journal of Psychosocial Rehabilitation, 2020)
The paper is dedicated to difficulties of applying particle 了 le in Chinese. The authors emphasize that applying particle 了 le is one of the most considerable difficulties in the Chinese language in terms of grammar. The issues related to the use of particle le on difficulties of applying particle 了 le in the Chinese language are of great current interest as learners often make mistakes when they have to apply the particle. The purpose of the work is to show a wide range of particularities regarding particle 了 le in the Chinese language. The novelty of the paper is that the authors have given a full analysis of specific varieties for the use of particle 了 le in different situations. The article incorporates 11 paragraphs and each paragraph is dedicated to different situations with regard to the particle. A number of examples have been given to underline the problems of the issue. One of the most considerable difficulties of the Chinese language in terms of grammar is the particle 了. Particle le may be viewed as the most difficult aspect for foreign learners to learn and understand Chinese. It can be explained by a wide range of application and immense variety of functions.